Genomic selection in sheep: prospects for Indian sheep industry - L.L.L. Prince; G.R. Gowane (Indian Journal of Veterinary and Animal Sciences Research, 2025)
Small ruminants are the key component among the livestock sector that plays a significant role in sustainable livelihood of landless and small holder farmers in India. Rural human population constitutes 72.22 % out of which majority are dependent directly or indirectly on the agriculture and livestock related occupations. The total sheep in the country is 65.06 million that accounts for nearly 12.7% of total livestock population in India.Traditional breeding programs aimed at improving the productivity of sheep through selection. Nevertheless accurate, this approach always relied upon the intensity of selection and length of the generation interval (GI). Larger the GI, more time it took to improve any given trait of interest. Since advent of the genomic selection, genomic estimated breeding values (GEBV) of animals are being obtained at juvenile stage. This has resulted in significant reduction in the generation interval and faster rate of genetic improvement with more accuracy. Single Step approach has further allowed use of even non-genotyped individuals in reference for better accuracy and less bias of prediction. Genomic selection has literally replaced the pedigree selection at many places across the world barring India. In our country given the large population, sheep breeds can be easily brought under the genetic improvement programs and hence the benefits to the sheep industry can be increased many-fold. In India, given large sheep genetic resources which are yet to be included in the improvement programs due to lack of pedigree relationship can be very well brought under this umbrella. Genomic selection can be effectively used to enhance the pace and accuracy of selection programs especially for the traits which are difficult to measure, expressed in one sex and late in life or post death and have low heritability.